Impact of Rural Trauma Team Development Education on Prehospital Time, Referral-to-Dispatch Interval, and Neurological and Musculoskeletal Injury Outcomes: Cluster Randomized Controlled Trial - Lule, Herman; Mugerwa, Micheal; Abio, Anne; Oguttu, Benson; Kakeeto, Andrew; Walsh, Fiona J.; Lekuya, Hervé Monka; Ssebuufu, Robinson; Kyamanywa, Patrick; Deckert, Andreas; Bärnighausen, Till; Posti, Jussi P.; et al. (JMIR Publications Inc., 2026)
Background:
Scarce human resources for health and high injury-related mortality coincide with inequities in accessing quality trauma education programs in low- and middle-income countries. Existing observational studies restrict assessments of trauma training program impacts on providers’ knowledge. Evaluation of trauma education programs outside clinical trial settings hinders their effectiveness in influencing clinical practice and policy changes for patient outcomes.
Objective:
This study aimed to assess the impact of the Rural Trauma Team Development Course (RTTDC) on clinical processes and patient outcomes of motorcycle-accident–related neurological and/or musculoskeletal injuries in selected Ugandan hospitals.
Methods:
This was a pragmatic 2-arm, parallel, multiperiod, cluster randomized controlled trial. The participants were trauma care frontline personnel and patients aged 2‐80 years at 3 intervention and 3 control Ugandan hospitals (1:1 allocation). Hospitals were randomly allocated to intervention or control groups using permuted block sequences. Sequence codes were generated off-site by an independent statistician using Sealed Envelope (version 1.23.1; Sealed Envelope Ltd). Both patient participants and outcome assessors were blinded to allocation. Hospital allocation codes were concealed until the point of assignment. In the intervention arm, 500 trauma care frontliners received RTTDC, whereas patients received standard care. In the control arm, patients received standard care without RTTDC for staff. The primary outcomes were time from accident to admission and from referral to dispatch. The secondary outcomes were all-cause 90-day mortality and morbidity related to neurological and/or musculoskeletal injuries. We followed the CONSORT (Consolidated Standards of Reporting Trials) guidelines for reporting cluster randomized trials.
Results:
We analyzed 1003 participants (501 intervention and 502 control). The intervention arm had a shorter median (IQR) prehospital time of 1 hour (0.50‐2) and referral-to-dispatch interval during interfacility transfers of 2 hours (1.25‐2.75). This contrasted with 2 hours (1.50‐4) and 4 hours (2.50‐4.10) in the control arm, respectively (P<.001). The 90-day mortality was more than halved in the intervention (5%, 24/457) vs in the control arm (13%, 58/430) (P<.001). Fewer participants in the intervention group had unfavorable Glasgow Outcome Scale scores (9%, 42/457) vs (20%, 87/430) (P<.001). No difference was found in musculoskeletal injury morbidity outcomes (P=.57).
Conclusions:
Rural trauma team development training demonstrated potential for improved organizational time efficiency and clinical outcomes for neurological injuries without negatively impacting musculoskeletal injury morbidity outcomes. Evidence from this trial supports that locally contextualized, trainee-led rural trauma team development interventional programs are feasible in low- and middle-income countries. However, despite being a multicenter study conducted across 6 geographically distinct hospitals, the research is limited in generalizability due to its focus on a single health care system within 1 country, retrospective trial registration, exclusion of prehospital deaths, and a relatively small number of clusters, which could introduce measurement bias.